Além da materialidade do teto: o Conjunto Habitacional Jardim Vitória em Belo Horizonte - Tais de Paula Barbosa Sousa (2016)
The deployment of the idea about the right to decent housing runs through a perspective that goes beyond the physical occupation of the territory. Is is today, in a multidimensional way, the symbolic and social framework in which is located the majority of human beings. In 2009, amid a backdrop of economic crisis, the housing program "Minha Casa, Minha Vida" is released, facing the real estate financing of ready housing for people with income between 0 to 10 minimum wages. In the first phase, between 2009 and 2011, the partnership between public and private sectors promoted 400,000 social housing in Brazil for families with a monthly income of up to 3 minimum wages. It is this type of housing and this type of public that this masters dissertation focuses through the case study of the Jardim Vitória Housing Complex and its 1,470 housing units in Belo Horizonte, capital of Minas Gerais. The focus is on the experience of the beneficiaries and how the construction of this project raises questions about the social housing policy Minha Casa Minha, Vida: how far it is to provide beneficiaries the right to the city and to decent housing?